Protocol for a Multicenter, Double-Blind, Randomized Controlled Trial on Jal Neti: Current Trends, Standardization of Process, and Clinical Efficacy - Dasarathan Sathyanath; Satya Lakshmi Komarraju; Kajal Gupta; Shivangi Pandey; Shrikanth Muralidharan (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Jal Neti, a traditional yogic nasal irrigation technique, has shown potential in managing chronic rhinosinusitis and upper respiratory conditions. However, lack of standardization and limited high-quality evidence hinder its integration into clinical practice. Materials and Methods: This multicenter, double-blind, randomized controlled trial is conducted across seven yoga and naturopathy institutions in India. In Phase 1, an observational study assessed current Jal Neti practices. In Phase 2, 270 healthy participants aged 18–60 were randomized into nine groups receiving different combinations of water temperature (room temperature, 34.7°C, 42°C) and saline concentration (0, 5, 9) for nasal irrigation. Results: The trial aims to determine the optimal parameters (saline concentration, pH, temperature) for Jal Neti practice and compare its efficacy with standard saline sprays. Data analysis will employ appropriate statistical tools with P < 0.05 as significance threshold. Conclusion: This study will provide standardized, evidence-based guidelines for Jal Neti, supporting its role as a complementary therapy for respiratory health in integrative medicine.